An Outbreak of Clostridium (Clostridioides) difficile Infections within an Acute and Long-Term Care Wards Due to Moxifloxacin-Resistant PCR Ribotype 176 Genotyped as PCR Ribotype 027 by a Commercial Assay - Novakova, Elena; Kotlebova, Nina; Gryndlerova, Anezka; Novak, Martin; Vladarova, Michala; Wilcox, Mark; Kuijper, Ed; Krutova, Marcela (Journal of clinical medicine, 2020)
We aimed to characterize Clostridioides difficile isolates cultured during a six-month single-center study from stool samples of patients with C. difficile infection (CDI) genotyped by the Xpert®C. difficile/Epi assay by polymerase chain reaction (PCR) ribotyping, toxin genes' detection and multi-locus variable number tandem repeats analysis (MLVA). The susceptibility to metronidazole, vancomycin and moxifloxacin was determined by agar dilution. In addition, the presence of Thr82Ile in the GyrA and a single nucleotide deletion at position (Δ117) in the tcdC gene were investigated. Between January 1 and June 30, 2016, of 114 CDIs, 75 cases were genotyped as presumptive PCR ribotype (RT) 027 infections using a commercial assay. C. difficile isolates cultured from presumptive RT027 stool samples belonged to RT176. These isolates carried genes for toxin A (tcdA), B (tcdB), binary (cdtA/B) and had Δ117 in the tcdC gene. Using MLVA, the 71/75 isolates clustered into two clonal complexes (CCs). Of these, 39 isolates (54.9%) were from patients hospitalized in acute care and 32 isolates (45.1%) were isolated from patients hospitalized in the long-term care department. All isolates were susceptible to metronidazole and vancomycin, and 105 isolates were resistant to moxifloxacin (92%) carrying Thr83Ile in the GyrA. An outbreak of RT176 CDIs, suspected as RT027, was recognized in a Slovakian hospital. In order to monitor the emergence and spread of RT027-variants, the identification of a presumptive RT027 CDI should be confirmed at a strain level by PCR ribotyping.